Gênero nas aulas de educação física: diálogos possíveis com os conteúdos do currículo do Estado de São Paulo e o Facebook - Milani, Amanda Gabriele [UNESP] (2015)
This study aimed to: a) observe and analyze the relationships between young people in physical education classes the first year of high school regarding the gender perspective; b) propose and analyze pedagogical interventions in conjunction with a physical education teacher at a public school, aiming to reflect on the theme of gender from the contents of the curriculum of the State of São Paulo and c) analyze how ICT can assist in the development facebook the theme Gender in Physical Education classes. We used qualitative method, and the research was divided into three stages. At first there was a diagnosis of how the teacher and the students understand the gender issue. In the second stage was prepared jointly with the teacher, pedagogical intervention proposals for the inclusion of gender issues in the classroom. In the third step, a closed group on facebook was created to promote gender discussions among school actors. Data collection occurred by observing the teacher's lessons, analysis of posts held in the facebook group, semi-structured interviews with teachers and students, and analysis of field diaries, and the data analyzed using content analysis. The results were expressed in three categories, the first Approach to the field: the contextualization of school and physical education classes, it was found that the school is adapting the model school full-time. The observed students had a good interaction between the sexes, but in gender relations with a male dominance was seen in a while. The developer teacher showed advances in their practice. However, there was a separation of boys and girls in some activities. In the second category of analysis, Society and Gender, were discussed gender stereotypes in society and the separation of boys and girls in physical education classes. Although not identified significant change in the teacher's discourse, it positively evaluated the collaborative work. Most students said they had learned...